Women’s Empowerment and Gender-Related Factors Associated with Maternal Tetanus Protection in 39 Low- and Middle-Income Countries - Katherine Kirkby; Luisa Arroyave; Franciele Hellwig; M. Carolina Danovaro-Holliday; Nasir Yusuf; Shirin Heidari; Stephanie Shendale; Aluísio J. D. Barros; Ahmad Reza Hosseinpoor (Vaccines, 2025)
Background: Tetanus is a vaccine-preventable disease, and therefore vaccination of women of reproductive age or during pregnancy is recommended alongside childhood tetanus vaccination. Gender-related factors related to social empowerment have been established as determinants of health service utilization; however, these social determinants have not yet been explored directly with tetanus vaccination. In response, the aim of this study was to assess overall and country-specific gender-related barriers to maternal tetanus vaccine coverage. Methods: We used data from Demographic and Health Surveys (DHS) in 39 countries implemented between 2013 and 2022. Women’s empowerment was measured through three domains of the Survey-based Women’s emPowERment index (SWPER), as well as other gender-related variables. To assess the association between measures of women’s empowerment and gender-related factors and maternal tetanus immunization coverage, we used multilevel logistic models with pooled data from the 39 countries to analyze overall patterns, and we used multivariable logistic regression for each country-specific dataset to analyze country-level associations. Results: There were notable variations in the factors associated with tetanus vaccination across countries. Overall, we observed that higher levels of women’s empowerment, as measured through social independence and decision-making autonomy using the SWPER index, were associated with higher odds of maternal tetanus protection, with adjusted odds ratios of 1.23 (95%CI: 1.10–1.37) and 1.20 (95%CI: 1.02–1.40), respectively. However, women’s empowerment related to attitude to violence was not. Higher household wealth was also associated with higher odds of maternal tetanus protection overall. Conclusions: Women’s empowerment can improve the uptake of maternal tetanus vaccine. Addressing gender-related barriers may enhance vaccination coverage and contribute to the elimination of maternal and neonatal tetanus as a public health problem. However, these barriers vary from country to country, necessitating country-specific investigations to formulate tailored recommendations.